Learning Planning Communication Strategiesfostering Student Growth Mindset According to The Character of Pancasila Student Profile - Dayati, Sri Wahyuning; Masodah, Masodah (Journal of Social Science and Education Research, 2024)
This study aims to develop a learning planning communication strategy to foster student growth mindset in accordance with the Pancasila Student Profile. Growth mindset is important in growing student character. Students need to be taught how to cultivate a growth mindset by introducing the difference between a fixed mindset and a growth mindset. Cultivating a growth mindset in the classroom requires a learning planning communication strategy. This research uses a library research approach. This research is descriptive qualitative. The technique used is to reduce reference books and journals that discuss growth mindset. This research resulted in three things. First, produce management and communication planning learning strategies that can foster a growth mindset. Learning planning communication strategies include planning, organizing, implementing and evaluating. The media used is the Canva application. Through a power point created in the Canva application, you can easily connect to YouTube as a new media. Second, produce a communication design for learning communication programs for growth mindset teaching materials. Third, produce students who have a growth mindset character that strengthens and grows the character of the Pancasila Student Profile.